A Promising Material by Using Residue Waste from Bisphenol A Manufacturing to Prepare Fluid-Loss-Control Additive in Oil Well Drilling Fluid - Zhi-Lei Zhang; Feng-Shan Zhou; Yi-He Zhang; Hong-Wei Huang; Ji-Wu Shang; Li Yu; Hong-Zhen Wang; Wang-Shu Tong (Journal of Spectroscopy)
The residues mixture from Bisphenol A manufacturing process was analyzed. Fourier transform infrared (FTIR) spectroscopy, gas chromatography-mass spectrometry (GC-MS), and nuclear magnetic resonance (NMR) were used to characterize the residues. The results indicated that the residues were complex mixture of several molecules. 3-(2-Hydroxyphenyl)-1,1,3-trimethyl-2,3-dihydro-1H-inden-5-ol and phenol were the main components of the residues. The technical feasibility of using it as phenol replacement in fluid-loss-control additive production was also investigated. The fluid-loss-control capacity of the novel additive was systematically investigated. It was discovered that the well fluid-loss performance of the prepared additive can be achieved, especially at high temperature.